Respostas ecofisiológicas e bioquímicas do Ocimum basilicum L. cultivado em diferentes níveis hídricos - Vargas, Maria Eliane de Oliveira (2007)
The sustainable development of northern agroecosystems requires, among other factors, the use of species adapted to region the edafoclimtic conditions. Plants able to support water deficits are more indicated, considering to no regular distribution of pluviometric precipitation the high evapotranspiration are characteristic northest region of Brazil. The present work was carried out to determine the ecofisiologic and biochemistry behavoir of three cultivars of basil, Ocimum basilicum L. (Maria Bonita, Mara and Genovese) cultivated under water stress. The ecofisiologics variables were: hidric potential of leaves, photossintesis, transpiration, stomatal conductance; the biochemitry variables were: soluble carbohydrates and proteins, totals cloroplasts, tenor of essential oil and percentage of linalool. The varibles were analyzed in plants with four months of aged, cultivated in 24 vases of 17L, in greenhouse, having two treatments: T0 (control) and T1 (experimental group), with four repetitions. The variables were evaluated at 08:30 to 10:30 hours every two days, during 15 days in October 2005. In base of results it was identifyed that basil presents mechanisms of adaptation under water stress minimizing the water lose. Mara’and Maria Bonita’cultivars presented more adaptaded under water stress in comparison with ‘Genovese’cultivar. In relation to the essential linalool content the three cultivars kept their yield even under water stress. It was observed the geraniol presence in Maria Bonita cultivar.